Handbook of medical imaging. Volume 2, - Sonka, Milan; Fitzpatrick, J. Michael (SPIE Press, 2000)
Volume 2 addresses the methods in use or in development for enhancing the visual perception of digital medical images obtained by a wide variety of imaging modalities and for image analysis as an aid to detection and diagnosis.
Keywords: Diagnostic imaging -- Digital techniques -- Handbooks, manuals, etc.; Imaging systems in medicine -- Handbooks, manuals, etc.; elektronické knihy; electronic books